Navigating Cross-Cultural Communication in International Business Negotiations: Insights and Strategies for Effective Negotiation Outcomes - Prawiraharja Cahya; Dwi Aryanti Semnani (Kampret Journal, 2024)
Cross-cultural communication plays a pivotal role in international business negotiations, yet it presents complex challenges that can significantly impact negotiation outcomes. This research explores the intricacies of cross-cultural communication in international business negotiations, aiming to provide insights into the impact of cultural differences on communication styles and negotiation strategies, the role of language and non-verbal communication, and effective strategies for managing cross-cultural communication challenges. Using a mixed-methods approach, data was collected through semi-structured interviews and surveys with experienced negotiators and professionals in international business. Thematic analysis of qualitative data and statistical analysis of quantitative data were conducted to identify patterns, trends, and insights relevant to the research objectives. The findings reveal the critical importance of cultural intelligence and adaptability in navigating cross-cultural communication challenges. Negotiators who demonstrate high levels of cultural intelligence and adaptability are more successful in understanding and respecting cultural differences, adapting communication styles, and building rapport with counterparts from different cultural backgrounds.